The impact of formal and non – formal education on youth employability in Bosnia and Herzegovina - Pilav-Velić Amila; Jahić Hatidža; Okičić Jasmina; Kokorović-Jukan Meldina (Croatian Review of Economic, Business and Social Statistics, 2019)
Education plays a central role in today’s understanding of growth and development dynamics. However, its relationship with other factors is complex. This paper aims to investigate the effect of different forms of education on youth employability in Bosnia and Herzegovina. This is done by using the USAID MEASURE – BiH National Youth Survey. Research has shown that formal education and non-formal education through internship programmes, volunteering, paid jobs other than internships are significant predictors of youth employment status. The study also has several implications for academics and practitioners since it provides new insights into both employment patterns and practices in one transition economy but also calls for further analysis of the link between education, formal and non-formal, and youth employment.